Anti-fogging heat-blocking membrane, anti-fogging heat-blocking paint, and anti-fogging heat-blocking film

JP7641172B2Active Publication Date: 2025-03-06MITSUBISHI MATERIALS ELECTRONICS CHEM CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021079998
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-10
Publication Date
2025-03-06
Estimated Expiration
2041-05-10

Smart Images

  • Figure 0007641172000005
    Figure 0007641172000005
  • Figure 0007641172000006
    Figure 0007641172000006
  • Figure 0007641172000001
    Figure 0007641172000001
Patent Text Reader

Abstract

To provide a heat ray cutting film with an anti-fogging function, a heat ray cutting paint with an anti-fogging function and a heat ray cutting film with an anti-fogging function that are superior in a heat ray cutting performance and also superior in an anti-fogging function and transparency.SOLUTION: A heat ray cutting film with an anti-fogging function has indium tin oxide (ITO) particles and a glycerin compound as an anti-fogging agent dispersed uniformly in a transparent resin, wherein a ratio (%Ts) / (%Tv) of solar transmittance (%Ts) to visible light transmissivity (%Tv) is 0.83 or less, and an angle of contact with water is 20 degrees or less. The film includes 0.8 to 5 g / m2 of ITO particles and 0.04 to 1.4 g / m2 of the glycerine compound, respectively, the ITO particles have a specific surface area of 30 m2 / g or larger measured by a BET method and also have a dark-blue color tone with lightness L* of 30 or less, and chromaticity a*<0 and chromaticity b*<0 defined by a CIE1976 L*a*b* color system, and the glycerine compound is glycerol fatty ester etc.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat ray cut-off film with anti-fogging function that is required for window glass of houses, offices, vehicles, ships, etc. that have windows through which sunlight enters, and that has heat ray (infrared ray) blocking and anti-fogging properties, a paint for forming this heat ray cut-off film with anti-fogging function, and a film having this heat ray cut-off film with anti-fogging function. [Background technology]

[0002] During the day, sunlight enters the windows of houses, offices, vehicles, ships, etc., causing the temperature inside the room and inside the vehicle to rise. For this reason, by installing this type of heat-blocking film on the window glass, the rise in the temperature inside the room and inside the vehicle can be suppressed. On the other hand, in the cold and rainy seasons, the humidity inside the room and inside the vehicle becomes high. For this reason, air conditioning equipment is operated in dehumidification mode.

[0003] As a conventional heat ray cut-off film, the present applicant has proposed a heat ray cut-off film that is excellent in heat ray cut-off performance, as well as in anti-fogging and anti-fouling functions and transparency (see Patent Document 1 (Claim 1, paragraph

[0005] )). This heat ray cut-off film is a heat ray cut-off film in which indium tin oxide (ITO) particles are uniformly dispersed in a transparent resin, and the ITO particles are dispersed at a density of 0.6 g / m in the heat ray cut-off film. 2 ~14g / m 2 0.15 g / m of an amphoteric nitrogen-containing fluorine-based compound was used as a membrane surface conditioner. 2 The ITO particles are 30m 2 / g~65m 2 / g and an L value of 50 or less, a contact angle with water of 30 degrees or less, a contact angle with n-hexadecane of 50 degrees or more, and a ratio of solar transmittance (%Ts) to visible light transmittance (%Tv) ((%Ts) / (%Tv)) of 0.83 or less.

[0004] Meanwhile, a coating-type anti-fogging agent for agricultural films has been disclosed that can impart not only initial anti-fogging properties (immediate anti-fogging effect) but also long-term anti-fogging properties to agricultural films, and the coated agricultural films have transparency (see, for example, Patent Document 2 (Claim 1, paragraph

[0008] ). This agricultural synthetic resin film has a surface coating containing colloidal inorganic fine particles such as alumina and silica, a water-soluble alkali metal silicate, and a synthetic resin as active ingredients. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6680543 [Patent Document 2] International Publication No. WO2019 / 004007 Summary of the Invention [Problem to be solved by the invention]

[0006] In the heat-ray-cutting film disclosed in Patent Document 1, when the heat-ray-cutting film is provided on a vertical window glass via a base film, the amphoteric nitrogen-containing fluorine-based compound contained in the heat-ray-cutting film does not adhere sufficiently to the other components contained in the heat-ray-cutting film, and although the initial anti-fogging property is high, over time the amphoteric nitrogen-containing fluorine-based compound continues to absorb moisture in the air, causing it to flow downward, and therefore this heat-ray-cutting film has a problem in that it does not provide a sustained anti-fogging effect.

[0007] Therefore, it is conceivable to use an anti-fogging agent containing colloidal inorganic fine particles such as alumina and silica, a water-soluble alkali metal silicate, and a synthetic resin as shown in Patent Document 2, which can impart not only initial anti-fogging properties (immediate anti-fogging effect) but also long-term anti-fogging properties, instead of the amphoteric nitrogen-containing fluorine-based compound shown in Patent Document 1. However, when a heat-cutting film with anti-fogging function is formed by using a combination of this alumina and silica as an anti-fogging agent together with the ITO particles shown in Patent Document 1, there is a problem that the haze of the film increases and the transparency of the film is not high.

[0008] The object of the present invention is to provide a heat ray-cutting film with anti-fogging function which has excellent heat ray-cutting performance as well as excellent anti-fogging function and transparency, a paint for forming this heat ray-cutting film, and a film having this heat ray-cutting film with anti-fogging function. [Means for solving the problem]

[0009] A first aspect of the present invention is a heat-cutting film with anti-fogging function (hereinafter, sometimes simply referred to as a film or a heat-cutting film), which is formed by uniformly dispersing indium tin oxide (ITO) particles and a glycerin compound as an anti-fogging agent in a transparent resin, has a ratio ((%Ts) / (%Tv)) of solar radiation transmittance (%Ts) to visible light transmittance (%Tv) of 0.83 or less, and has a contact angle with water of 20 degrees or less, and is characterized in that the ITO particles are contained in the film at a concentration of 0.8 g / m. 2 ~5g / m 2 The glycerin compound is added at a ratio of 0.04 g / m 2 ~1.4g / m 2 and the ITO particles have a specific surface area of ​​30 m according to the BET method. 2 / g or more and CIE1976L * a * b * Lightness L defined by the color system * is 30 or less, chromaticity a * <0 and chromaticity b * <0, and the glycerin compound is a glycerin fatty acid ester, a diglycerin fatty acid ester, or a polyglycerin fatty acid ester.

[0010] A second aspect of the present invention is a heat ray cut paint with anti-fogging function for forming a heat ray cut film with anti-fogging function of the first aspect (hereinafter, may be simply referred to as a paint for forming a heat ray cut film or a heat ray cut paint), which contains indium tin oxide (ITO) particles, a glycerin compound as an anti-fogging agent, a transparent resin, and a solvent, and is characterized in that, when the solid content of the paint is 100 mass%, the ITO particles are contained in a ratio of 4 mass% to 78 mass%, and the glycerin compound is contained in a ratio of 1 mass% to 8 mass%, respectively.

[0011] A third aspect of the present invention is a heat-cutting film with anti-fog function, which comprises a transparent substrate film having the heat-cutting film with anti-fog function of the first aspect on one side thereof, and a pressure-sensitive adhesive layer and a release film laminated in this order on the other side opposite to the one side thereof, and has a haze of 2.0% or less. Effect of the Invention

[0012] The heat ray cut-off film with anti-fogging function according to the first aspect of the present invention is a heat ray cut-off material having a specific surface area of ​​30 m2 as measured by the BET method. 2 / g or more and CIE1976L * a * b * Lightness L defined by the color system * is 30 or less, chromaticity a * <0 and chromaticity b * <0, and the ITO particles are present in the film at a concentration of 0.8 g / m 2 ~5g / m 2 This results in a film with a ratio of solar radiation transmittance (%Ts) to visible light transmittance (%Tv) of 0.83 or less ((%Ts) / (%Tv)), giving the film excellent transparency and heat ray blocking performance. In addition, a glycerin compound is added as an anti-fogging agent in the film at a concentration of 0.04 g / m 2 ~1.4g / m 2Since the content of the glycerin compound is in the range of 0.1 to 1.0%, the contact angle of water is 20 degrees or less, and the anti-fogging function is excellent. In particular, since the glycerin compound contains an acyl group, the adhesion to the substrate is relatively excellent, and unlike the amphoteric nitrogen-containing fluorine-based compound shown in Patent Document 1, the anti-fogging property is excellent not only in the initial anti-fogging property (immediate anti-fogging effect) but also in the long-term anti-fogging property. In addition, since the glycerin compound is a transparent substance, unlike the anti-fogging agent containing colloidal inorganic fine particles, water-soluble alkali metal silicate, and synthetic resin shown in Patent Document 2, the haze of the film is not increased and the transparency of the film is not reduced.

[0013] The coating material for forming a heat ray-cutting film with anti-fogging function according to the second aspect of the present invention contains ITO particles and a glycerin compound in a predetermined ratio depending on the thickness of the film to be formed, and therefore has excellent heat ray-cutting performance, anti-fogging function and transparency.

[0014] In the heat ray cut film with anti-fogging function according to the third aspect of the present invention, the release film is peeled off and the base film having the heat ray cut film with anti-fogging function is adhered to a window glass via the adhesive layer, thereby cutting off heat rays (infrared rays) among the sunlight incident on the window glass. Even if the humidity inside the room rises, the haze is 2.0% or less, so that the anti-fogging effect is achieved without causing fogging. [Brief description of the drawings]

[0015] [Figure 1] 1 is a cross-sectional view of the configuration of an anti-fogging heat-cut film according to an embodiment of the present invention. [Diagram 2] FIG. 1 is a cross-sectional view showing the state in which this film is adhered to a window glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Next, an embodiment of the present invention will be described.

[0017] [Anti-fogging heat-blocking coating paint] The coating material for forming a heat ray cut-off film with an antifogging function of the present embodiment contains ITO particles having a heat ray cut-off function, a transparent resin that transmits visible light, and a glycerin compound as an antifogging agent.

[0018] The ITO particles have a specific surface area of ​​30 m2 by the BET method. 2 / g or more, preferably 32m 2 / g~73m 2 / g, CIE1976L * a * b * Lightness L defined by the color system * is 30 or less, chromaticity a * <0 and chromaticity b * <0. Preferably, the color has a deep blue color with a lightness L * is 29 or less, chromaticity a * is -1.0 or less and chromaticity b * is -1.0 or less. If the specific surface area of ​​the ITO particles measured by the BET method is less than the lower limit of the above range, the haze of the heat ray cut-off film increases and the transparency of the film decreases. If the content of ITO particles in the film is reduced in order to reduce the haze, the heat ray cut-off function of the film cannot be obtained. The lightness L of the ITO particles * exceeds 30, and chromaticity a * is 0 or more and chromaticity b * If it is 0 or more, the heat ray blocking function is inferior.

[0019] The transparent resin in the coating material may be any resin that transmits visible light and has adhesiveness to the substrate of the heat-shielding film, and is preferably an ionizing radiation curable resin. When the coating material contains an ionizing radiation curable resin, a polymerization initiator such as a photopolymerization initiator is added to obtain a coating material for forming a heat-shielding film. Examples of the transparent resin include urethane (meth)acrylate, polyester (meth)acrylate, epoxy (meth)acrylate, melamine (meth)acrylate, triazine (meth)acrylate, and other resins.

[0020] The ionizing radiation curable resin can be used without any particular limitation as long as it has film-forming properties, transparency, and adhesiveness to the substrate of the heat-ray cut film, for example, an ionizing radiation curable resin capable of forming a crosslinked film such as an ultraviolet-curable or electron-beam-curable resin. Among them, an ultraviolet-curable resin containing a photopolymerization initiator in a monomer or oligomer containing one or more of an acrylic compound or an epoxy compound has film-forming properties, transparency, and hard coat properties, does not require a separate hard coat layer to be laminated on the heat-ray cut film, and is excellent in adhesiveness to the substrate of the heat-ray cut film, so it is preferable. Examples of the photopolymerization initiator include acetophenone compounds and benzoin compounds. The amount of the photopolymerization initiator added is preferably in the range of 0.1% by mass to 10% by mass relative to the ultraviolet-curable resin. If the amount added is less than 0.1% by mass or more than 10% by mass, ultraviolet curing is likely to be insufficient.

[0021] The paint for forming the heat-cutting film with anti-fogging function is prepared by mixing ITO particles, a transparent resin, a glycerin compound, and a solvent. A dispersant may be mixed into this paint. By mixing a dispersant, the transparency of the coating film is further improved.

[0022] The paint for forming the heat ray cut-off film with anti-fogging function of this embodiment forms a heat ray cut-off film of 1 m 2 In order to keep the number of ITO particles per coating constant regardless of film thickness, the content of ITO particles is changed according to film thickness. To form a thin heat-ray-cutting film, the number of coats is reduced or the content of ITO particles in the paint solids, i.e., the concentration of ITO particles, is increased. On the other hand, to form a thick heat-ray-cutting film, the number of coats is increased or the content of ITO particles in the paint solids, i.e., the concentration of ITO particles, is decreased.

[0023] When the solid content of the paint is 100% by mass, the ITO particles are contained in a proportion of 4% to 78% by mass, the glycerin compound is contained in a proportion of 1% to 8% by mass, and when the solid content of the paint is 100% by mass, the components other than the ITO particles are contained in a proportion of 14 to 95% by mass. In this case, the preferred content of the ITO particles is 20% to 70% by mass, and the preferred content of the glycerin compound is 2% to 7% by mass.

[0024] If the content of ITO particles in the paint solids is less than 4 mass%, the heat-cutting function of the heat-cutting film made from this paint cannot be improved, and if the content of ITO particles exceeds 78 mass%, the paint thickens and its stability over time deteriorates, and there is a relative shortage of transparent resin, which reduces the adhesive strength between the ITO particles and deteriorates the heat-cutting function of the heat-cutting film.

[0025] If the content of components other than ITO particles in the paint solids is less than 14% by mass, the heat-ray-cutting film will not adhere sufficiently to the substrate, and if the content exceeds 95% by mass, the paint will thicken, reducing stability over time and impairing the heat-ray-cutting function of the heat-ray-cutting film.

[0026] Furthermore, if the content of the glycerin compound as an anti-fogging agent in the paint solids is less than the lower limit of the above range, the anti-fogging function of the film will be inferior, and if it exceeds the upper limit of the above range, the paint will thicken, for example, and its stability over time will deteriorate, resulting in a decrease in the heat-ray blocking function of the heat-ray blocking film.

[0027] The glycerin compound as the antifogging agent of the present embodiment may be glycerin fatty acid ester, diglycerin fatty acid ester, or polyglycerin fatty acid ester. Examples of the glycerin fatty acid ester include glycerin monostearate, glycerin monobehenate, glycerin monooleate, glycerin monocaprylate, glycerin monolaurate, glycerin monodistearate, and glycerin monodiolate. Examples of the diglycerin fatty acid ester include diglycerin monocaprylate, diglycerin monolaurate, diglycerin monostearate, and diglycerin monooleate. Examples of the polyglycerin fatty acid ester include tetraglycerin stearate, tetraglycerin oleate, hexaglycerin laurate, hexaglycerin oleate, decaglycerin laurate, and decaglycerin stearate.

[0028] Since the solvent in the paint is required to dry quickly, it is preferable to use a combination of low boiling point solvents such as 2-butanone, 4-methyl-2-pentanone, ethanol, 2-propanol, 1-butanol, toluene, methanol, 1-propanol, ethyl acetate, butyl acetate, acetone, 2,4-pentanedione, xylene, etc., and high boiling point solvents such as 3-methoxy-3-methyl-1-butanol, diacetone alcohol, etc., in order to improve film-forming properties. The content of the solvent is preferably 45% by mass to 95% by mass, when the paint is taken as 100% by mass.

[0029] The dispersant in the coating material is preferably contained in an amount of 1 to 10 parts by mass per 100 parts by mass of ITO particles. As an example of the dispersant, any pigment dispersant can be used as long as it can stably disperse the pigment into particles. Specifically, alkyl ether sulfates such as ammonium polyoxyethylene styrenated phenyl ether sulfate, sodium polyoxyalkylene decyl ether sulfate, sodium polyoxyethylene tridecyl ether sulfate, ammonium polyoxyethylene isodecyl ether sulfate, sodium polyoxyethylene lauryl ether sulfate, ammonium polyoxyethylene lauryl ether sulfate, sodium polyoxyethylene alkyl ether sulfate, ammonium polyoxyethylene oleyl cetyl ether sulfate, and sodium polyoxyethylene oleyl cetyl ether sulfate, alkyl sulfates, alkyl benzene sulfonates, alkyl phthalene sulfonates, polyoxyethylene alkyl ether phosphates, polyoxyethylene alkyl ether phosphates, polyoxyethylene lauryl ether sulfate, and the like. Examples of the surfactant include alkyl phosphate salts such as telluric acid esters, polyoxyethylene alkyl ether phosphates, polyoxyethylene tridecyl ether phosphates, and polyoxyethylene styrenated phenyl ether phosphates, alkyl ether acetates such as polyoxyethylene alkyl ether acetates, and sodium polyoxyethylene lauryl ether acetates, alkyl succinates such as disodium lauryl sulfosuccinate, disodium polyoxyethylene alkyl sulfosuccinate, disodium lauryl polyoxyethylene sulfosuccinate, and polyoxyethylene alkyl sulfosuccinates, anionic surfactants such as polycarboxylic acid type polymers, cationic surfactants such as amine oxides, and nonionic surfactants such as oxyethylene block copolymers and polyoxyethylene alkylamides. If the content of the dispersant is less than 1 part by mass, the dispersion of the coating material for forming the anti-fogging heat-cutting film is insufficient, and the transparency of the coating film is likely to be insufficient. If the content of the dispersant exceeds 10 parts by mass, the film strength of the anti-fogging heat-cutting film and the adhesion of the coating film are likely to be adversely affected.

[0030] [Anti-fogging and heat-blocking film] The heat ray cut-off film with anti-fogging function of the present embodiment is made by uniformly dispersing ITO particles in a transparent resin and containing a glycerin compound as an anti-fogging agent. This heat ray cut-off film contains ITO particles at a density of 0.8 g / m 2 ~5g / m 2 At a ratio of 0.04 g / m2, glycerin compounds were added. 2 ~1.4g / m 2 In this case, the preferred content of ITO particles is 1 g / m 2 ~4g / m 2 The preferred content of the glycerin compound is 0.1 g / m 2 ~1.0g / m 2 The specific surface area of ​​ITO particles measured by the BET method and CIE1976L * a * b * Lightness L defined by the color system * , chromaticity a * and chromaticity b * The range is as described above. The transparent resin is preferably contained in the heat ray cut-off film in an amount of 14% by mass to 90% by mass. When the ITO particles, the transparent resin and the glycerin compound have the above properties and are contained in the heat ray cut-off film, a heat ray cut-off film with an anti-fogging function is obtained, in which the ratio ((%Ts) / (%Tv)) of the solar radiation transmittance (%Ts) to the visible light transmittance (%Tv) is 0.83 or less and the contact angle of water is 20 degrees or less.

[0031] The content of ITO particles in the heat-cut film with anti-fogging function is 0.8 g / m 2 If the content of ITO particles is less than 5 g / m, the heat-shielding function of the heat-shielding film will not improve. 2 If the thickness exceeds 100 nm, the visible light transmittance will drop to 70% or less, and transparency will not be achieved. * a * b * Lightness L defined by the color system * , chromaticity a * and chromaticity b *The critical values ​​of the respective numerical ranges and the critical values ​​of the ranges of the content of the glycerin compound are the same as the critical values ​​of the respective numerical ranges in the paint.

[0032] The heat-ray-cutting film with anti-fogging function of this embodiment is formed, for example, by applying the above-mentioned coating material for forming a heat-ray-cutting film with anti-fogging function onto a substrate such as glass or a polyester film such as polyethylene terephthalate (PET), polybutylene terephthalate, or polyethylene naphthalate by screen printing, bar coating, die coating, doctor blade, spinning, or the like, followed by drying at a temperature of 60°C to 130°C, and, if the transparent resin is an ionizing radiation-curable resin, by irradiating with ionizing radiation.

[0033] [Anti-fog heat-blocking film] As shown in Fig. 1, when the substrate is a transparent substrate film 10, the above-mentioned anti-fogging heat-cutting film 11 is formed on one side of the transparent substrate film 10, and an adhesive layer 12 and a release film 13 are laminated in this order on the other side opposite to the one side of the transparent substrate film. In this way, an anti-fogging heat-cutting film 14 is produced. The haze of this anti-fogging heat-cutting film is 2.0% or less. The thickness of the transparent substrate film 10 is, for example, 10 μm to 300 μm, preferably 20 μm to 200 μm. The adhesive layer 12 is not particularly limited as long as it has adhesiveness to glass and is transparent, and examples thereof include acrylic resin, polyester resin, urethane resin, polyvinyl butyral, and copolymers thereof. The thickness of the adhesive layer 12 is not particularly limited, but is preferably 0.5 μm to 100 μm, and more preferably 1 μm to 80 μm. The adhesive layer 12 can be provided by a known coating technique. The release film 13 can be appropriately selected from known ones. For example, one side of a plastic substrate such as polyethylene terephthalate is silicone-treated.

[0034] As shown in Fig. 2, when this heat ray cut film 14 with anti-fogging function is applied to window glass 15 through which sunlight enters, the release film 13 shown in Fig. 1 is peeled off and the adhesive layer 12 is adhered to the indoor surface of the window glass 15. In this way, the heat ray cut film 11 with anti-fogging function is positioned on the indoor side, blocking heat rays entering from the outside and preventing fogging due to humidity generated indoors during cold and rainy seasons. EXAMPLES

[0035] Next, examples of the present invention will be described in detail together with comparative examples.

[0036] [Preparation of paint for forming heat-cutting film with anti-fogging function] <Example 1> The specific surface area according to the BET method is 55m 2 / g, CIE1976L * a * b * Lightness L defined by the color system * is 21.3, chromaticity a * is -2.8 and chromaticity b * ITO particles having a deep blue color tone with a pH of -2.3 were prepared. 100g of these ITO particles were added to a mixture of 10g of polyoxyethylene alkyl ether phosphate ester-based dispersant and 140g of industrial alcohol (manufactured by Japan Alcohol Industry Co., Ltd., AP-7) as a solvent, and dispersed with a bead mill disperser to obtain an ITO dispersion with an ITO concentration of 40% by mass. 31g of the obtained ITO dispersion, 31g of urethane acrylic emulsion liquid as a binder, 1g of a reaction product of dodecanoic acid and diglycerol as an anti-fog agent, 0.3g of an alkylphenone-based polymerization initiator as a photopolymerization initiator, 10g of industrial alcohol (manufactured by Japan Alcohol Industry Co., Ltd., AP-7), and 26g of water were mixed to prepare a heat-cut paint with anti-fog function with a solid concentration of 30% by mass so that the thickness of the coating film after drying would be 3 μm. When the solid content of this paint was 100% by mass, the paint contained 51.2% by mass of ITO particles, 4.7% by mass of glycerin monodistearate as an anti-fogging agent, and 44.1% by mass of urethane acrylate resin as a transparent resin. The details of the preparation are shown in Table 1 below.

[0037] [Table 1]

[0038] <Examples 2 to 6 and Comparative Examples 1, 2, 4 to 7> In Examples 2 to 6 and Comparative Examples 1, 2, and 4 to 7, the type of ITO particles and the type of glycerin compound as an antifogging agent were selected as shown in Table 1, and the contents of the ITO particles, glycerin compound, and urethane acrylate resin were set as shown in Example 1. Otherwise, the heat-cut coating materials with antifogging function of Examples 2 to 6 and Comparative Examples 1, 2, and 4 to 7 were prepared in the same manner as in Example 1.

[0039] <Comparative Example 3> In Comparative Example 3, as shown in Table 1, the same ITO particles and urethane acrylate resin as in Example 1 were used. As the antifogging agent, a mixture of Al2O3, SiO2, acetic acid, acrylic resin, and aluminum water-soluble salt (SW-25 manufactured by Riken Vitamin Co., Ltd.) shown in Patent Document 2 was selected. As shown in Example 1, the respective contents of the ITO particles, the mixture, and the urethane acrylate resin were set. Otherwise, the same procedure as in Example 1 was followed to prepare the heat-cut paint with antifogging function of Comparative Example 3.

[0040] <Comparative Example 8> In Comparative Example 8, as shown in Table 1, the same ITO particles and urethane acrylate resin as in Example 1 were used. As the antifogging agent, the sulfobetaine type nitrogen-containing fluorine-based compound shown in the following formula (1) used in Example 1 of Patent Document 1 was selected. As shown in Example 1, the respective contents of the ITO particles, the sulfobetaine type nitrogen-containing fluorine-based compound, and the urethane acrylate resin were set. Otherwise, the same procedure as in Example 1 was followed to prepare the heat-cut coating material with antifogging function of Comparative Example 8.

[0041] [ka]

[0042] [Formation of anti-fogging heat-blocking film] The anti-fog heat-blocking paints obtained in Examples 1 to 6 and Comparative Examples 1 to 8 were used to form 14 different coating films with different thicknesses on a polyethylene terephthalate (PET) substrate film with a thickness of 0.05 mm, a length of 300 mm, and a width of 200 mm, using various types of bar coaters (manufactured by Yasuda Seiki Seisakusho). The 14 types of coating films were dried in an air atmosphere at 80°C, and the dried coating films were then irradiated with ultraviolet light at a dose of 150 mJ / cm. 2 Fourteen types of heat-cutting films with anti-fogging properties were obtained by irradiating the films with a laser microscope (OLS5100, manufactured by Olympus Corporation) to measure the thickness of the films obtained.

[0043] [Comparative testing and evaluation] The contents of ITO particles and antifogging agent in the 14 types of heat-cutting films with antifogging function were measured by the following method. The measurement results are shown in Table 2 below.

[0044] [Table 2]

[0045] In addition, the transparency of the heat-cutting film with anti-fog function on 14 types of base film was evaluated by measuring the visible light transmittance (%Tv), solar radiation transmittance (%Ts), and haze, and the ratio of solar radiation transmittance (%Ts) to visible light transmittance (%Tv) ((%Ts) / (%Tv)) was calculated. The water wettability of the heat-cutting film surface and the adhesion of the heat-cutting film to the base film were evaluated using the methods shown below. Furthermore, an anti-fog test was conducted to evaluate the anti-fog property and wiping durability of the film on the film surface, and a test to evaluate the heat-shielding performance of the film was also conducted. The results are shown in Table 3 below.

[0046] [Table 3]

[0047] (1) Contents of ITO particles and anti-fogging agent in the heat-shielding film with anti-fogging function The film mass was obtained from the mass difference between the substrate film before and after the antifogging heat-cutting film was formed. Next, the obtained antifogging heat-cutting film was dissolved in acid to recover the film components. The indium concentration in the recovered liquid was quantified by ICP emission spectrometry, the ITO particle concentration (mass%) was calculated, and the ITO particle content was calculated from the film mass. In addition, the obtained heat-cutting film was scraped off the substrate film and recovered, and the antifogging agent concentration (mass%) was calculated from the pyrolysis GC-MS (Gas Chromatography-Mass Spectrometry) and compound formula.

[0048] (2) Transparency (visible light transmittance (%Tv), solar transmittance (%Ts), and haze) For the heat-cut film with anti-fog function on the base film, a spectrophotometer (U-4150 manufactured by Hitachi High-Technologies Corporation) was used to measure the visible light transmittance (% Tv) of 380 nm to 780 nm including the base film in accordance with the standard (JIS R 3106-2019), and the solar radiation transmittance (% Ts) of 300 nm to 2500 nm including the base film was measured. Haze was also measured using a haze computer (HZ-2 manufactured by Suga Test Instruments Co., Ltd.) in accordance with the standard (JIS K 7136). The visible light transmittance, solar radiation transmittance, and haze listed in Table 3 are values ​​including the base film, and the visible light transmittance of the base film alone was 87.6%, the solar radiation transmittance was 87.4%, and the haze was 1.4%.

[0049] (3) Water wettability of the film surface (contact angle) Using a Dropmaster DM-700 manufactured by Kyowa Interface Science, ion-exchanged water at 22°C ± 1°C was prepared in a syringe, and a 2μL droplet was ejected from the tip of the needle of the syringe. Next, the anti-fogging heat-cut film on the substrate film to be evaluated was brought close to the droplet, and the droplet was attached to the heat-cut film. The contact angle of the attached water was measured. The contact angle after 1 second when the water touched the film surface in a stationary state was analyzed by the θ / 2 method, and the value was taken as the contact angle of water, and the water wettability of the film surface was evaluated.

[0050] (4) Film adhesion The adhesion of the obtained anti-fog heat-cut film to the base film was tested by a checkerboard test. Specifically, 100 squares were cut into one sheet of the film on the base film, and a peeling test was performed using tape. When the number of squares of the film peeled off from the base film was "0," it was judged as "good," and when the number of squares of the film peeled off from the base film was "1 or more," it was judged as "poor."

[0051] (5) Anti-fogging properties of the film surface The obtained anti-fog heat-cut film on the substrate film was kept for a specified time in a thermo-hygrostat kept at 40°C and a relative humidity of 90%. The condition of each film was visually checked after 8 hours and after 1 week of keeping. If there was no fogging, it was judged as "good", and if there was fogging, it was judged as "poor".

[0052] (6) Wipe-off durability of the film The surface of the heat-cutting film with anti-fog function on the base film was wiped 20 times with a water-soaked cellulose nonwoven fabric (Pencot M-3, Asahi Kasei Corporation) at a constant weight. If the film remained after wiping, it was judged as "good", and if even a part of the film was missing, it was judged as "bad".

[0053] (7) Heat shielding performance test An infrared lamp (IR250 manufactured by Iwasaki Electric), a base film with a heat-cutting film with anti-fogging function, a base film without this film, and a thermometer were prepared. The base film was fixed vertically at a position 10 cm away from the infrared lamp in the direction of irradiation. The thermometer was fixed at a position 5 cm behind the base film, further away from the infrared lamp. The infrared lamp was irradiated, and the temperature was measured after 60 seconds. The temperatures of the base material without the film and the base material with the film were compared. A difference of 5°C or more was judged as "good", a difference of 2°C or more but less than 5°C was judged as "slightly good", and a difference of less than 2°C was judged as "poor".

[0054] As is clear from Table 1, in Comparative Example 1, the specific surface area of ​​the ITO particles by the BET method was 28 m 2 / g and the particles were large, so the haze of the heat-cutting film with anti-fog function including the base film was high at 2.6%, and the transparency of the film was low.

[0055] In Comparative Example 2, the L of ITO particles * is 60.1, a * is 0.4, b * The ratio of solar transmittance (%Ts) to visible light transmittance (%Tv) ((%Ts) / (%Tv)) was 0.93, which was high. Therefore, the result of the heat shielding performance test was "poor", and the heat ray blocking function was poor.

[0056] In Comparative Example 3, the anti-fog agent shown in Patent Document 2 was used as the anti-fog agent, and therefore the compatibility was poor when mixed with resin and ITO particles, so the haze of the heat-cut film with anti-fog function including the base film was high at 5.3%, and the transparency of the film was low. In addition, the adhesion of the film was "poor", and the results of the anti-fog test were "good" both after 8 hours and after 1 week, but the wipe durability was "poor".

[0057] In Comparative Example 4, the content of ITO particles in the film was 0.6 g / m 2 Because the amount of the material was too little, the ratio of solar transmittance (%Ts) to visible light transmittance (%Tv) ((%Ts) / (%Tv)) was high at 0.84. As a result, the result of the heat shielding performance test was "poor," and the material had poor heat-blocking capabilities.

[0058] In Comparative Example 5, the content of ITO particles in the film was 6.4 g / m 2 Because the amount was too much, the haze of the heat-blocking film with anti-fog function including the base film was high at 2.3%, and the transparency of the film was low. In addition, the adhesion of the film was "poor", and the results of the anti-fog test were "good" both after 8 hours and after 1 week, but the wipe durability was "poor", indicating poor anti-fog properties.

[0059] In Comparative Example 6, the content of the antifogging agent in the film was 0.03 g / m 2Because the amount of water was too little, the water contact angle of the film surface was as large as 26 degrees, making it difficult for the film to become wetted with water. As a result, in the anti-fogging test, the film was rated as "poor" both after 8 hours and after 1 week, and the wipe-off durability was also rated as "poor," indicating poor anti-fogging properties.

[0060] In Comparative Example 7, the content of the antifogging agent in the film was 1.80 g / m 2 Because the amount was too much, the haze of the heat-blocking film with anti-fog function including the base film was high at 2.4%, and the transparency of the film was low. The adhesion of the film was also "poor". Furthermore, the wipe durability was also "poor", and the anti-fog properties were poor.

[0061] In Comparative Example 8, the antifogging agent disclosed in Patent Document 1 was used as the antifogging agent, and therefore the adhesion of the film was "poor." The result of the antifogging test after 6 hours was "good," but because it continued to absorb moisture in the air, the result of the antifogging test after 1 week was "poor."

[0062] In contrast, in Examples 1 to 6, a glycerin compound was used as the antifogging agent, and the content of the glycerin compound was 0.04 g / m 2 ~1.4g / m 2 Therefore, the water contact angle of the film surface was 20 degrees or less, and it was easily wetted by water. Therefore, the results of the anti-fogging test of the film were all "good" after 8 hours and 1 week, and the wiping durability was also all "good", showing excellent anti-fogging properties. Furthermore, the content of ITO particles in the film was 0.8 g / m 2 ~5g / m 2 The specific surface area of ​​the ITO particles in the film is in the range of 30 m by the BET method. 2 / g or more, the haze of the film including the base film was good at 2% or less. In addition, the (%Ts) / (%Tv) value was 0.83 or less, and the heat ray blocking performance was also satisfactory. [Industrial Applicability]

[0063] The heat ray cut-off film with anti-fogging function of the present invention is used in fields requiring heat ray (infrared ray) cut-off and anti-fogging properties, such as in window glass of houses, offices, vehicles, ships, etc. that have windows through which sunlight can enter. [Explanation of symbols]

[0064] 10 Transparent substrate film 11 Anti-fogging and heat-blocking film 12 Adhesive layer 13 Release film 14 Anti-fog heat-blocking film 15 Window Glass

Claims

1. A heat ray cut film with an anti-fogging function, which is formed by uniformly dispersing indium tin oxide (ITO) particles and a glycerin compound as an anti-fogging agent in a transparent resin, has a ratio ((%Ts) / (%Tv)) of solar radiation transmittance (%Ts) to visible light transmittance (%Tv) of 0.83 or less, and has a contact angle of water of 20 degrees or less, In the film, the ITO particles are 0.8 g / m 2 ~5g / m 2 The glycerin compound is mixed at a ratio of 0.04 g / m 2 ~1.4g / m 2 Each of them includes The ITO particles have a specific surface area of ​​30 m as measured by the BET method. 2 / g or more and CIE1976L * a * b * Lightness L defined by the color system * is 30 or less, chromaticity a * <0 and chromaticity b * <0, 1. A heat-cutting film with anti-fogging function, wherein the glycerin compound is a glycerin fatty acid ester, a diglycerin fatty acid ester or a polyglycerin fatty acid ester.

2. A heat ray cut paint with anti-fogging function for forming the heat ray cut film with anti-fogging function according to claim 1, comprising indium tin oxide (ITO) particles, a glycerin compound as an anti-fogging agent, a transparent resin, and a solvent, The heat-blocking paint with anti-fogging function is characterized in that, when the solid content of the paint is 100 mass%, the ITO particles are contained in a ratio of 4 mass% to 78 mass%, and the glycerin compound is contained in a ratio of 1 mass% to 8 mass%.

3. 1. A heat-cutting film with anti-fog function, comprising the heat-cutting film with anti-fog function according to claim 1 on one side of a transparent substrate film, and an adhesive layer and a release film laminated in this order on the other side of the transparent substrate film opposite to the one side of the transparent substrate film, and having a haze of 2.0% or less.

Citation Information

Patent Citations

  • Dispersion composition of ito fine particle, composition for interlayer for laminated glass, interlayer by using the same, and laminated glass

    JP2001233643A

  • Agricultural film

    JP2010081808A

  • Heat ray shielding composition and method for manufacturing the same

    JP2011116623A

  • Heat ray cut film and coating for forming the heat ray cut film

    JP2017128661A

  • Heat-shielding film and paint for forming this heat-shielding film

    JP6680543B2